Effects of Tootling on Classwide and Individual Disruptive and Academically Engaged Behavior of Lower‐Elementary Students. (18th April 2016) - McHugh, Melissa B.; Tingstrom, Daniel H.; Radley, Keith C.; Barry, Christopher T.; Walker, Kelly M.
Abstract : The current study was designed to replicate and extend the literature on the effectiveness of a classroom intervention known as Tootling, a strategy that encourages and prompts students to report instances of their peers' positive behaviors. The purpose of the present study was to assess the effects of the Tootling intervention on decreasing classwide and individual target students' disruptive behavior as well as increasing classwide and individual target students' academic engagement in lower elementary, general education classrooms using a criterion number of tootles that could reasonably be attained daily, thus potentially allowing more immediate and frequent access to reinforcement. Participants included second and third graders and their teachers in three classrooms in two Southeastern elementary schools. An ABAB withdrawal design was used in the three classrooms, along with a multiple baseline element across two of the classrooms, to determine the effectiveness of the intervention. Results demonstrated decreases in disruptive behaviors and increases in academically engaged behaviors during intervention phases as compared to baseline and withdrawal phases in all classrooms. Effect sizes were moderate to large for all comparisons. Limitations of the present study, directions for future research, and implications for practice are discussed. Copyright © 2016 John Wiley & Sons, Ltd.